2014
DOI: 10.1021/jo5012575
|View full text |Cite
|
Sign up to set email alerts
|

A Chemoenzymatic Synthesis of Hept-6-ene-2,5-diol Stereomers: Application to Asymmetric Synthesis of Decarestrictine L, Pyrenophorol, and Stagonolide E

Abstract: The stereomers of hept-6-ene-2,5-diol derivatives were conceived as useful chiral intermediates and were synthesized starting from sulcatol using two lipase-catalyzed acylation reactions as the key steps. The versatility of the intermediates was demonstrated by converting them to the titled tetrahydropyran, macrolide, and macrodiolide compounds using standard synthetic protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 97 publications
1
23
0
Order By: Relevance
“…The 1 H and 13 C NMR spectral data of 3 showed great similarity to those of 2 (Table 1) 9), and C-9 (from d C 68.7 to d C 67.0). Extensive analysis of the 1 H NMR, 13 C NMR, HSQC, HMBC, and 1 H-1 H COSY spectra of 3 inferred that 3 had the same planar structure as 2.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…The 1 H and 13 C NMR spectral data of 3 showed great similarity to those of 2 (Table 1) 9), and C-9 (from d C 68.7 to d C 67.0). Extensive analysis of the 1 H NMR, 13 C NMR, HSQC, HMBC, and 1 H-1 H COSY spectra of 3 inferred that 3 had the same planar structure as 2.…”
Section: Introductionmentioning
confidence: 68%
“…7 These simple macrodiolides possess promising biological activities and unique structures which make them attractive synthetic targets. [8][9][10] While natural 18-membered macrodiolide were few. 1,11 Previous study reported four novel aliphatic phenolic ethers from fungus Trichobotrys effuse.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, both key intermediates (3 S ,6 R )-acetate and (3 R ,6 S )-alcohol were obtained with high enantioselectivity ( E > 195), c 50%. The enantiomerically pure (3 R ,6 S )-alcohol was used as an intermediate in the synthesis of Stagonolide E. The chemoenzymatic synthesis of Pyrenophorol and Decarestrictine L involved the enantiomericaly pure allylic (3 S ,6 R )-acetate as key intermediate ( Scheme 32 ) [ 52 ].…”
Section: Esterification Approachmentioning
confidence: 99%
“… Kinetic enzymatic acylation of rac -hept-6-ene-2,5-diol derivatives to produce key intermediates in the synthesis of the Stagonolide E, Pyrenophorol and Decarestrictine L [ 52 ]. …”
Section: Esterification Approachmentioning
confidence: 99%
“…[775]; (13) macrocyclic bis(lactone)s, including those employed in syntheses of C-glycosphingolipids [776], pyrenophorol (also includes cross metathesis employing an acrylate ester in an earlier step of the synthesis, plus a methyl vinyl ketone cross metathesis for synthesis of decarestrictine L and an acrolein cross metathesis for synthesis of a related lactone stagonolide E) [777], 4-ketoclonostachydiol (e.g. 309) [778]; (14) macrocyclic tris(lactone)s, including those employed for preparation of macrosphelide I [779], and a macrosphelide A-biotin chimera [780]; (15) macrocyclic keto-lactone for total synthesis of amphidinolide Y precursors [781]; (16) macyoclic lactone-furanophanes, including those employed for syntheses of the plumarellide ring system (e.g.…”
Section: )mentioning
confidence: 99%